2018
DOI: 10.24138/jcomss.v13i4.364
|View full text |Cite
|
Sign up to set email alerts
|

Towards Robust Communications of Wireless Sensor Networks in Vehicular Environments: A Case Study

Abstract: Wireless Sensor Networks are popular solutions for various applications in order to reduce the efforts required by traditional cable-based systems. If the system in question is used to monitor and control physical processes, robust and reliable communication services have to be provided by the network. This is especially true for industrial or vehicular applications where the nodes are deployed in environments facing harsh propagation conditions. Usually, the effect of this on the system performance is studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…for diagnostic applications. In addition, exploring potential usages for query based wireless communication between components of a single vehicle scenarios might be promising since it has been shown that these suffer from a massive packet loss when using higher data rates and uncoordinated transmissions due to packet collisions [29].…”
Section: Discussionmentioning
confidence: 99%
“…for diagnostic applications. In addition, exploring potential usages for query based wireless communication between components of a single vehicle scenarios might be promising since it has been shown that these suffer from a massive packet loss when using higher data rates and uncoordinated transmissions due to packet collisions [29].…”
Section: Discussionmentioning
confidence: 99%
“…Improving vehicular networks for reliable communications is a hard challenge [5]- [7]. One of the first steps to solve it is to assess the wireless link quality.…”
Section: Related Workmentioning
confidence: 99%